mRNA-miRNA networks identify metabolic pathways associated to the anti-tumorigenic effect of thyroid hormone on preneoplastic nodules and hepatocellular carcinoma - Serra, Marina; Pal, Rajesh; Puliga, Elisabetta; Sulas, Pia; Cabras, Lavinia; Cusano, Roberto; Giordano, Silvia; Perra, Andrea; Columbano, Amedeo; Kowalik, Marta Anna (Frontiers in Oncology, 2022)
Background: Thyroid hormones (THs) inhibit hepatocellular carcinoma (HCC) development and progression through different mechanisms. However, it remains unknown whether microRNAs (miRs) play a role in the antitumorigenic effect of THs. Methods: By Next Generation Sequencing (NGS), we analyzed miRNAs and mRNAs in the very same samples and performed a comprehensive comparative expression profiling of rat hepatic preneoplastic nodules exposed or not to a short-term treatment with triiodothyronine (T3). The expression of the most deregulated miRs was also investigated in rat HCCs and in human hepatoma cell lines, treated or not with T3. Results: Co-expression networks identified miRs targeting thyroid hormone receptor-β (THRβ), deiodinase (Dio1) and Oxidative Phosphorylation among the most down-regulated miRs in preneoplastic nodules following T3 treatment. On the other hand, miRs targeting members of the Nrf2 Pathway, Glycolysis, Pentose Phosphate Pathway and Proline biosynthesis – all involved in the metabolic reprogramming displayed by preneoplastic lesions – resulted up-regulated. Notably, while the expression of most miRs deregulated in preneoplastic lesions was not altered in HCC or in human hepatoma cells, only miR-182, a miR known to target Dio1 and mitochondrial complexes, resulted down-regulated by T3 treatment at all stages of hepatocarcinogenesis, as well as in HCC cell lines. In support to the important role of miR-182 in hepatocarcinogenesis, exogenous expression of this miR significantly impaired the inhibitory effect of T3 on the clonogenic growth capacity of human HCC cells. Conclusions: This work identifies for the first time several miRs regulated by the thyroid hormone and so far, never associated to it. In addition, the precise definition of the miRNA-mRNA networks elicited by T3 treatment gained in this study provides a better understanding of the key regulatory events underlying the inhibitory effect of T3 on HCC development and progression. In this context, T3-induced down-regulation of miR-182 appears as a new promising tool for HCC management.